1990
DOI: 10.1128/aem.56.1.120-126.1990
|View full text |Cite
|
Sign up to set email alerts
|

Intermediary Metabolite Concentrations in Xylulose- and Glucose-Fermenting Saccharomyces cerevisiae Cells

Abstract: Glucose and xylulose fermentation and product formation by Saccharomyces cerevisiae were compared in batch culture under anaerobic conditions. In both cases the main product was ethanol, with glycerol, xylitol, and arabitol produced as by-products. During glucose and xylulose fermentation, 0.74 and 0.37 g of cell mass liter-', respectively, were formed. In glucose-fermenting cells, the carbon balance could be closed, whereas in xylulose-fermenting cells, about 25% of the consumed sugar carbon could not be acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 27 publications
(28 reference statements)
2
27
1
Order By: Relevance
“…The maximum speci¢c growth rate on xylulose increased upon TAL overproduction, supporting the hypothesis that TAL activity limits pentose metabolism in S. cerevisiae [1,9,13]. Overproduction of TAL increased the aerobic growth on solid xylose media of a XYL1/XYL2-expressing strain [9] as measured by visual inspection of cell mass after 3 days.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The maximum speci¢c growth rate on xylulose increased upon TAL overproduction, supporting the hypothesis that TAL activity limits pentose metabolism in S. cerevisiae [1,9,13]. Overproduction of TAL increased the aerobic growth on solid xylose media of a XYL1/XYL2-expressing strain [9] as measured by visual inspection of cell mass after 3 days.…”
Section: Discussionsupporting
confidence: 68%
“…Flux modelling has shown that the £ux through the reaction catalysed by RPE is very low in anaerobic xylose fermenting S. cerevisiae TMB3001 [12]. The nonoxidative PPP intermediate sedoheptulose 7-phosphate accumulates both in xylose-fermenting [1] and in xylulosefermenting [13] S. cerevisiae, suggesting insu⁄cient transaldolase activity. Overexpression of transaldolase leads to faster aerobic growth on xylose [9], but not to faster xylose fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…The low xylose fermentation rate in recombinant S. cerevisiae has been suggested to result from transport limitation [24] and from an insu⁄cient PPP £ux [25]. In this investigation we conclude that also the XR activity partly controls the xylose consumption rate.…”
Section: Discussionmentioning
confidence: 52%
“…This means that in S. cerevisiae other factors like activities of other enzymes may be limiting, e.g. transaldolase, as sedoheptulose 7-phosphate has been shown to accumulate in D-xylulose fermentation [20].…”
Section: The Expression Of Xylulokinase Had No E¡ect On the Growth Ramentioning
confidence: 99%